Congenital Epidermolysis Bullosa Epidemiology among Children of Russian Federation - Nikolay N. Murashkin; Roman V. Epishev; Olga S. Orlova; Alena А. Kuratova; Victoriya S. Polenova (Вопросы современной педиатрии)
Background. The prevalence of all types of congenital epidermolysis bullosa (СEB) worldwide is approximately 11 cases per 1 million according to the latest data from the American Epidermolysis Bullosa Registry. Data on the prevalence of СEB in Russian Federation is scattered, while data on life expectancy and mortality for this this disease is absent. This article presents medical and epidemiological data on children with СEB in Russian Federation. Objective. The aim of the study is to analyze clinical and epidemiological features of children with СEB in Russian Federation. Methods. We have performed analysis of the clinical and epidemiological features among pediatric population of Russian Federation with СEB using the “Registers of Genetic and Other Rare Diseases” of the “Butterfly Children” charitable foundation. Results. There are 491 children with СEB in Russian Federation as of 2024 according to the national registry data from “Registers of Genetic and Other Rare Diseases” of the “Butterfly Children” charitable foundation. The ratio of boys and girls was 1.08:1, that is relevant to the global data. The prevalence of CEB in children aged from 0 to 17 years in Russian Federation is 15.48 cases per 1,000,000 children as of January 1, 2024. The highest number of children with CEB were revealed in the Republic of Dagestan — 54 (11%) children, which is apparently due to the high rate of consanguineous marriages (50%). Other regions with high prevalence are Moscow Region (n = 28, 5.7%), Moscow (n = 25, 5.1%), Saint Petersburg (n = 26, 5.2%) and Krasnodar Territory (n = 23, 4.6%). Largest age group of children (from 12 to 18 years) includes 146 patients with mean age of 14.32 ± 1.72 years. The most common form of CEB is dystrophic one — 261 patients, the next one is simplex — 191 patients, then junctional form — 31 patient, and Kindler syndrome — 8 patients. The birth rate of children with CEB by year during the period from 2019 to 2023 (per 100,000 children born): 2019 — 1.42, 2020 — 2.09, 2021 — 2.65, 2022 — 2.76 and 2023 — 1.74. The arithmetic mean birth rate of children with CEB over a five-year period was 2.13 cases per 100,000 children born. The registry contains information on 22 deceased patients, average age was 3.06 ± 4.66 (from 0 to 15 years, median 0.54 years). The highest number of fatal outcomes was observed in the Republic of Dagestan (n = 3). Junctional CBE dominates in fatal outcomes among all the CEB types — 59.1% (n = 13 cases, 0.40 ± 0.22 years). The highest mortality was observed in I age group (from 0 to 1 year), which is 65.2% (15 fatal outcomes). Multisystem organ failure resulting from sepsis was the most common cause of death in both types of CEB (junctional and dystrophic). The mortality trend in the junctional form of CEB shows a decline in mortality, while the dystrophic type shows a stable situation during 2021–2023 years — 2 fatal outcomes per year. Junctional CEB has higher mortality rate at early age: survival curve shows sharp decline in the first months of life indicating high mortality in early life. The probability of survival drops to almost 0% in the first 100 days. Higher survival rate is more specific for the dystrophic type of CEB. Conclusion. This study demonstrates the significance and necessity to create and maintain registers for rare (orphan) diseases. Registry maintenance is an effective model for real understanding of the number of patients and value of needed assistance from the government to this category of patients.